THE PROBLEMS OF DEVELOPMENT OF TOURISM IN ARMENIA AND THE WAYS OF ITS SOLUTION - S. Petrosyan (Вестник университета)
Tourism is one the main branches of the economy of Armenia. It is accepted as the prior direction in all official levels. Tourism directly and indirectly has influence on the development of many economic spheres of the country. In the article the author did an analysis of tourism in Armenia and offers some important suggestions for solving the problems in that sphere and notifies.